Bacterial endophytes from Artemisia nilagirica (Clarke) Pamp., with antibacterial efficacy against human pathogens. (October 2019) - Ashitha, A.; Midhun, S.J.; Sunil, M.A.; Nithin, T.U.; Radhakrishnan, E.K.; Mathew, Jyothis
Abstract: A study was conducted to isolate and characterize endophytes from Artemisia nilagirica, a traditional medicinal plant. The plant was collected from Western Ghats, India. Endophytes isolated included Arthrobacter sp. WWAT1, Pseudomonas sp. WYAT2, Microbacterium sp. WYAT3, Psychrobacter sp. WBAT4, Enterobacter sp. WWAT5, Bacillus sp. WBAT6, Kosakonia cowanii WBAT7, Bacillus sp. WBAT8, Bacillus sp. WBAT9, Chromobacterium violaceum WVAT6, Serratia sp.WPAT8 and Burkholderia sp. WYAT7. Of these two bacteria, Chromobacterium violaceum strain WVAT6 and Burkholderia sp. strain WYAT exhibited antibacterial property against human pathogens. Similar to the environmental isolates, Burkholderia sp . WYAT7 showed pleomorphism and produced different enzymes, whereas like clinical strains they showed multidrug resistance, for their survival in different environmental conditions. Chromobacterium violaceum WVAT6 exhibited rod shape morphology and showed multiple drug resistance except to erythromycin, tetracycline and gentamicin antibiotics. Both produced biofilm and enzymes such as protease and lipase. The antimicrobial compounds from these endophytes may find application in the preparation of antimicrobial formulations. Highlights: 12 bacterial endophytes were identified. Remarkable antimicrobial activity of isolated endophytes against human bacterial pathogens. Chromobacterium violaceum WVAT6 and Burkholderia sp . WYAT7 exhibited antimicrobial resistance. The bacteria produced extracellular enzymes and biofilm.